Activation of Akt and the signaling of phosphorylated Akt in the L5 dorsal root ganglia in aging rats - Yon, H.M.; Naidu, M. (Elsevier, 2017)
Introduction Protein kinase B (PKB)/Akt is a kinase that is responsive towards insulin-like growth factor (IGF-1) and nerve growth factor (NGF). Detected in the cytosol, Akt is activated by phosphorylation at Thr308/Ser473 residue. The phosphorylated Akt (pAkt) is translocated into the nucleus via the of phosphatidylinositide 3-kinases (PI3K)-Akt pathway. Contradicting results have been reported on the expression of Akt and pAkt in aged animals. The study is conducted to determine the effect of aging on the Akt and pAkt signaling in the L5 dorsal root ganglia (DRG). Methods Twenty-four female Sprague-dawley rats were sacrificed at 3, 10, 20 and 27 months. L5 DRG was harvested and subjected to immunofluorescence staining. Results The expression of Akt and pAkt was detected in almost all neurons in all groups. Image analyzer analysis showed that the average intensity of Akt signaling increased from M10 to M27 compared to the M3. However, the average intensity of pAkt signaling was only significantly increased in M27 compared to the younger animals. Conclusion The expression of Akt and pAkt may indicate that increase activity is taking place in the aged neurons. The activation of Akt and its phosphorylation may be one of the mechanisms in response towards aging process.